Penggunaan Aplikasi Mendeley Untuk Peningkatan Kualitas Riset Akuntansi - Hengky Leon; Novianty Novianty (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to introduce lecturers and students to the importance of citations in scientific papers that can be poured into theses, theses, dissertations and even scientific articles. The activity method is applied by three methods, namely the lecture method, the practice method, and the evaluation method. The participants of the activity came from several lecturers and students in Pontianak totaling 12 participants with a time of 2.5 hours. The activity is carried out with an introduction to the citation of scientific papers and the importance of citations, especially in accounting research topics so that the citations taken are in accordance with the needs and lead to the field of accounting science itself. Then proceed with the process of explaining the understanding and use of mendeley. The results of this activity explained that all participants felt helped and could understand the process of using the mendeley application to improve the quality of accounting research. The weakness in this activity is that it takes more time for some participants who are slow to use the laptop or lack high mastery of the laptop. This activity is expected to have sustainability with an understanding of several models of writing forms needed according to needs.